Buda histórico y Buda legendario. Tradiciones hagiográficas de Siddhārtha Gautama - Arnau, Juan (El Colegio de México, 2013)
The article analyzes the various sources that have contributed to the legend of Siddhārtha Gautama: independent hagiographies such as the Lalitavistara or the Mahāvastu, the Buddhacarita of Aśvaghosa, Udāna, which constitutes the third section of the Khuddakanikāya and other fragments of the collections of the nikaya like the Nidānakathā, the hagiographies in monastic codes, collections of legends, tales and Indian tales collected in the genre ofthe jātaka-Canon. Finally some of the recent research around the dates of the historical Buddha’s life are synthesized.